Desenvolvimento de recheios de biscoito com redução de teor de gordura saturada e aplicação funcional - Rodrigues, Guilherme da Cruz (Universidade Federal de São Carlos, 2025)
Filled cookies present high levels of saturated fat, whose excessive intake has been associated with adverse health effects. This study aimed to develop cookie fillings with partial or total replacement of saturated fat by an organogel based on candelilla wax and supplemented with phytosterols, conferring functional potential. Five lipid systems were formulated with different proportions of vegetable fat and organogel (RC: 100:0; R1: 75:25; R2: 50:50; R3: 25:75; R4: 0:100; % w/w). The lipid fractions were characterized in terms of thermal cycling, oil binding capacity, and rheological properties, while the fillings were evaluated for water activity, color parameters, oil retention capacity, thermal stability, adhesion to the cookie, and mechanical properties. The lipid fractions remained stable and exhibited pseudoplastic behavior (η < 1), fitting the Herschel–Bulkley model (R² > 0.99), with yield stress ranging from 66.667 to 1.505 Pa and consistency index between 0.5303 and 0.749. The elastic modulus (G′) was higher in pure vegetable fat; however, organogel-containing blends showed a greater difference between G′ and G″, indicating a more pronounced solid-like behavior dependent on frequency. In the fillings, a darkening effect was observed, with luminosity decreasing from 30.28 to 11.05 as organogel concentration increased. Oil retention capacity remained stable after 15 days, with the highest oil loss observed in R4 (8.07%). Although lipid migration did not compromise adhesion, oil staining on the cookies was observed in all samples. After seven weeks, R3 exhibited the greatest resistance to deformation, being the least spreadable (68.68 N·s), the most adhesive (14.76 N·s), and the stickiest (3.47 N), whereas RC showed lower hardness (3.51 N), higher spreadability (20.25 N), and lower stickiness (1.45 N). Therefore, the incorporation of organogels enables a substantial reduction in saturated fat content in cookie fillings without compromising essential physicochemical and mechanical properties, representing a technologically feasible strategy aligned with current demands for healthier food products.
Development of cookie fillings with reduced saturated fat content and functional application
Keywords: Biscoito recheado; Organogéis; Gordura vegetal; Filled cookies; Organogels; Phytosterol; Fitoesterol; Vegetable fat; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::TECNOLOGIA DE ALIMENTOS; 2. Fome Zero e Agricultura Sustentável; 9. Indústria, Inovação e Infraestrutura